Structural Properties of Conjunction даи - Y. Wang (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
The constructive possibilities of the Russian coordinative conjunction да и is discussed. The work focuses on the types of conjunction structures with studied conjunction, their brief overview is given. Special attention is paid to the specificity of the compatibility of conjunction да и . The relevance of the study is determined by the need to have a complete understanding of the syntactic specifics of each conjunction, in particular, for its subsequent lexicographical description. The list of concretizations of the conjunction and their characteristic are given from the perspective of their role in each structure. Typical lexis that regularly combines with the conjunction да и is revealed. Distinction of the concepts of “concretization” and “typical lexis” is given on the basis of their functions in the structure. The novelty of the research is to identify the number of tokens, regularly combined with the conjunction and influencing the semantics of component of the structure imposed by the conjunction. The analysis establishes that the conjunction да и typically has a text function and a linking function in a complex sentence. The fact of formation of text brace on the basis of a combination да и потом is substantiated. It is concluded that concretization of the conjunction and typical lexis form the additional generalizing meaning in structures.